Sustainable Agriculture through Vermicomposting Technology - K Pattnaik, Ajoy; Mishra, Gopa (International Journal of Psychosocial Rehabilitation, 2025)
Vermicomposting is an environment friendly, low-technology method for the disposal of organic waste. It is the process in which the worms are used to convert the organic materials (usually wastes) into a humus-like material which is known as the vermin-compost. It is one of the easiest methods to recycle agricultural wastes and to produce quality compost. The resultant vermicompost produced is very beneficial for plant growth and health. The values, fertility and productivity of organic waste which has been returned to soil can be improved by beneficial impacts on soil resources and other processes. The production of organic wastes by the use of vermicompost technology is remarkably an effective technology for the reduction in processing time and also beneficial for the production of nutrients which are essential for the plants growth. It is a key component of the integrated plant nutrient supply system in order to maintain a healthy fertilization system along with maintaining safety. This organic fertilizer is considered to be present in both agriculture and horticulture as an alternative to the inorganic fertilizers in greenhouse media